2014
DOI: 10.15640/ijn.v1n2a14
|View full text |Cite
|
Sign up to set email alerts
|

Improving Clinical Competence and Confidence of Senior Nursing Students through Clinical Preceptorship

Abstract: Clinical preceptorship provides an essential aspect of nursing education for senior nursing students. This descriptive study identified perceptions of senior nursing students about their clinical preceptorship experiences, evaluated their perceived levels of competency and confidence in providing nursing care; and examined their perceived confidence level in relation to the perceived competency level of nursing skills. Researchers approached 134 culturally diverse senior nursing students enrolled in Preceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
(34 reference statements)
1
20
0
4
Order By: Relevance
“…A finding that concurred with Brehaut, Turik and Wade [34] and Yonge and Trojan's [35] work who found that preceptored students scored a higher percentage in relation to independent practice than the non-preceptored students , an element they related to ongoing contact with preceptors. Besides, students in Kim et al [36] pre and post preceptorship experience responses had differed markedly with students' perceived level of competency and confidence in providing nursing care showing higher scores in post-survey responses.…”
Section: Discussionmentioning
confidence: 96%
“…A finding that concurred with Brehaut, Turik and Wade [34] and Yonge and Trojan's [35] work who found that preceptored students scored a higher percentage in relation to independent practice than the non-preceptored students , an element they related to ongoing contact with preceptors. Besides, students in Kim et al [36] pre and post preceptorship experience responses had differed markedly with students' perceived level of competency and confidence in providing nursing care showing higher scores in post-survey responses.…”
Section: Discussionmentioning
confidence: 96%
“…In their research, Kim, Lee, Eudey and Wong Dea (2014) find that the level of students' perceived competences was positively correlated with the level of their interaction with the preceptor in clinical settings which lead to reconcile the role between nursing students and employers. Fan, Wang, Chao, Jane and Hsu (2015) state that nursing students must acquire competences in a clinical environment to close the gap between education and practice, and that nursing education should be based on competences-based learning.…”
Section: Employability and Employment Of Nursing Care Graduatesmentioning
confidence: 97%
“…An important component in achieving telementoring effectiveness has time and place-related challenges so that, synchronization needs to be done with the consistency of mentee and open communication. new nurses so that, nurses can work comfortably and securely so that, nurses are able to provide optimal service to patients (Kim et al, 2014).…”
Section: Effective Telementoringmentioning
confidence: 99%
“…So much of the benefits of applying mentoring to the nurse's development, regarding mentee's selfconfidence in making decisions (Kim, Young Lee, Eudey, & Wong Dea, 2014), are able to perform tasks better, and able to plan their careers in the learning process. Moreover, mentoring is also capable of improving job satisfaction, improving the ability to communicate with both patients and with other health workers, and lower stress levels of nurses (Bontrager, Hart, & Mareno, 2016;Lalonde & Mcgillis Hall, 2016).…”
Section: Introductionmentioning
confidence: 99%